MEMAHAMI HADIS NABI TENTANG KHITAN PEREMPUAN DARI PERSPEKTIF HISTORIS – FENOMENOLOGIS - Alamsyah, Alamsyah (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
Female circumcision is a present muslim societies‟tradition since ancient to modern times. Some moslemscholars say women do not need to be circumcised,but many other scholars argue for female circumcisionlaw is mandatory. They argue with hadith narrated byAbu Dawood from Umu Athiyah and narrated byAhmad from Osama. Scientifically studied these haditsis dha‟if can not be used as a basis in determining theproposition or obligation circumcision for girls. If atthe time of the Prophet Muhammad ever set of femalecircumcision, it should be understood only as hisijtihad itself, not as a permanent Sunnah, and justbecause people not be continue it. This is the wisdomof the Prophet who want to make changes to thetradition but performed by gradual and withoutcausing chaos.